2007
DOI: 10.1016/j.pcad.2007.03.001
|View full text |Cite
|
Sign up to set email alerts
|

The Bone Marrow—Cardiac Axis of Myocardial Regeneration

Abstract: Congestive heart failure remains the leading cause of morbidity and mortality in the developed world. Current therapies do not address the underlying pathophysiology of this disease, namely the progressive loss of functional cardiomyocytes. The notion of repairing or regenerating lost myocardium via cell based therapies remains highly appealing. The recent identification of adult stem cells, including both cardiac stem/progenitor cells and bone marrow stem cells, has triggered an explosive interest in utilizin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 116 publications
0
50
0
1
Order By: Relevance
“…In other words, things are promising at present and will likely get much better in the next few years with greater comprehension of the emerging stem cell regenerative medicine. It is easy to become enthused about relatively nascent observations of reverseengineered somatic cells, but it is far too early to become evangelical about their potential relative to what we have already got working [13]. Like so many other candidate stem cell types gone before them, capabilities and limitations of iPS cells remain to be defined, and I don't need to lecture you on the problems of ES cell-based therapy for cardiac repair [14].…”
Section: Murrymentioning
confidence: 99%
“…In other words, things are promising at present and will likely get much better in the next few years with greater comprehension of the emerging stem cell regenerative medicine. It is easy to become enthused about relatively nascent observations of reverseengineered somatic cells, but it is far too early to become evangelical about their potential relative to what we have already got working [13]. Like so many other candidate stem cell types gone before them, capabilities and limitations of iPS cells remain to be defined, and I don't need to lecture you on the problems of ES cell-based therapy for cardiac repair [14].…”
Section: Murrymentioning
confidence: 99%
“…The heart possesses regenerative capacity atributed to endogenous and exogenous progenitor cell populations [25]. Thus, there is a growing interest in developing new approaches to treat MI, cardiovascular tissue engineering is currently considered as a promising alternative therapy to restore the structure and function of infarcted adult myocardium via application of a biological device, onto the ischemic tissue [26].…”
Section: Tissue Regenerationmentioning
confidence: 99%
“…The first progeny of HSCs are multipotent progenitors that retain the ability to differentiate into all hematopoietic lineages but show a lower capacity to proliferate [59] [62] reported that mouse bone-marrow-derived cells give rise to skeletal muscle cells when transplanted into damaged mouse www.fhc.viamedica.pl muscle. Thereafter, transplanted bone marrow cells were reported to generate a wide spectrum of different cell types, including hepatocytes [63], endothelial, myocardial [64][65][66], neuronal, and glial cells [67,68]. Moreover, HSC can produce cardiac myocytes and endothelial cells [69], functional hepatocytes [70], and epithelial cells of the liver, gut, lung, and skin [71].…”
Section: Bone As a Source Of Adult Stem Cellsmentioning
confidence: 99%